PENGARUH MODERNIS TERHADAP TATA CARA ADAT PERKAWINAN SUKU BATAK TOBA DI DESA PETANI KECAMATAN MANDAU KABUPATEN BENGKALIS - Abdul Rahman Saputra; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research with the modernist phenomenon that has affected aspects of human life, including customs and old culture that has a lot left. The author would like to see want to see the influence of the modernist ordinances Toba Batak tribe marriage customs in rural districts farmer Saber district Bengkalis.Rumusan research problem is how the influence of the modernist Procedure Customary Marriages Batak Toba in Petani village Mandau sub Bengkalis. The purpose of this study to determine how the influence of the modernist Procedure Customary Marriage Batak Toba village farmer Saber Bengkalis districts. The population of this study were 421 responden.dengan using purposive sampling techniques so that the samples were taken by 43 respondents. Data collection instrument is a questionnaire with 21 questions about the influence of modernist and 17 questions about the manner of traditional wedding Batak tribe Toba.Terdapat significantly between modernist influences the manner of Toba Batak tribe marriage customs in rural districts farmers saber Bengkalis district. this is evidenced by a series of simple regression test between the variables X and Y, obtained F_hitung 1284dan F_tabel4,08 value obtained from the study of the distribution list F_tabel with N = 43, and is therefore F count> F table, or 1284> 4.08 So the hypothesis in this study which states that the Modernist influence on Procedure Customary marriages Batak Toba village farmers saber District of Bengkalis received.Keywords: modernist influences, Marriage Batak Toba